2005
DOI: 10.2741/1749
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of prostate cancer cellular proteasome activity by a pyrrolidine dithiocarbamate-copper complex is associated with suppression of proliferation and induction of apoptosis

Abstract: Recent research suggests that copper could be used as a novel selective target for cancer therapies. Copper is a co-factor essential for tumor angiogenesis processes and high levels of copper have been found in many types of human cancers, including prostate, breast and brain. We have reported that organic copper-containing compounds, such as 8-hydroxyquinoline-copper(II), are a novel class of proteasome inhibitors and tumor cell apoptosis inducers (Daniel et al., Biochem Pharmacol. 2004;67:1139-51). Most rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 36 publications
4
71
0
Order By: Relevance
“…Inhibition of the proteasomal activity leads to the accumulation of IκB-α, resulting in NF-κB inactivation. We have previously reported an ubiquitinated form of IκB-α protein with molecular weight of ~56 kDa (Chen et al, 2005a). A similar p56 band appeared after the treatment with 10 and 20 μmol/L PyDT-zinc and 1,10 and 20 μmol/L PyDT-copper mixture (Fig.…”
Section: Pydt-zinc Complex Is a Proteasome Inhibitor And An Apoptosissupporting
confidence: 59%
See 2 more Smart Citations
“…Inhibition of the proteasomal activity leads to the accumulation of IκB-α, resulting in NF-κB inactivation. We have previously reported an ubiquitinated form of IκB-α protein with molecular weight of ~56 kDa (Chen et al, 2005a). A similar p56 band appeared after the treatment with 10 and 20 μmol/L PyDT-zinc and 1,10 and 20 μmol/L PyDT-copper mixture (Fig.…”
Section: Pydt-zinc Complex Is a Proteasome Inhibitor And An Apoptosissupporting
confidence: 59%
“…However, when combined with either zinc(II) or copper(II) chloride, PyDT was shown to inhibit the ubiquitin-proteasome pathway (Kim et al, 2004;Daniel et al, 2005;Chen et al, 2005a). We have previously shown that PyDT-copper inhibits proliferation and induces apoptosis in cultured breast and prostate cancer cells by inhibiting proteasomal chymotrypsin-like activity (Daniel et al, 2005;Chen et al, 2005a). Based on that and similar location of zinc and copper in the periodic table, we hypothesized that the PyDT-zinc complex could have similar effect on the proteasome.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…14,15 Of these, PDTC is the most potent NFκB inhibitor. 16 PDTC has been shown to inhibit NFκB activation for suppressing tumor growth in colorectal cancer, 17 and for inducing pro-apoptotic and anti-proliferative effects in prostate cancer, 18 ovarian carcinoma cells, 19 breast cancer cells, 20 T-cell leukemia, 21 lymphoma, 22 gastric cancer cells 23 and renal cell carcinoma. 24 The expression of genes, such as vascular endothelial growth factor (VEGF), is also stimulated by NFκB, which is involved in angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor suppressive effects of DSF often depend on passive cellular uptake of this drug in complexes with copper. Copper ions were shown to be involved in regulation of dithiocarbamate-induced apoptosis of thymocytes, prostate cancer cells, astrocytes and melanoma cells (12,13,(15)(16)(17)(18). Recently, the copper-mediated inhibition of histone acetyltransferase activity and induction of apoptosis in pyrrolidine dithiocarbamate-treated leukemic cells have also been reported (19).…”
Section: Introductionmentioning
confidence: 99%